Strength of Interference Screw Fixation to Cuboid vs Pulvertaft Weave to Peroneus Brevis for Tibialis Posterior Tendon Transfer for Foot Drop. - Marsland,D; Stephen,JM; Calder,T; Amis,AA; Calder,JDF (Foot and Ankle International, 2018)
BACKGROUND: Tibialis posterior (TP) tendon transfer is an effective treatment for foot drop. Currently, standard practice is to immobilize the ankle in a cast for 6 weeks nonweightbearing, risking postoperative stiffness. To assess whether early active dorsiflexion and protected weightbearing could be safe, the current study assessed tendon displacement under cyclic loading and load to failure, comparing the Pulvertaft weave (PW) to interference screw fixation (ISF) in a cadaveric foot model. METHODS: Twenty-four cadaveric ankles had TP tendon transfer performed, 12 with the PW technique and 12 with ISF to the cuboid. The TP tendon was cycled 1000 times at 50 to 150 N and then loaded to failure in a materials testing machine. Tendon displacement at the insertion site was recorded every 100 cycles. An independent t test and 2-way analysis of variance were performed to compare techniques, with a significance level of P < .05. RESULTS: Mean tendon displacement was similar in the PW group (2.9 ± 2.5 mm [mean ± SD]) compared with the ISF group (2.4 ± 1.1 mm), P = .35. One specimen in the ISF group failed early by tendon pullout. None of the PW group failed early, although displacement of 8.9 mm was observed in 1 specimen. Mean load to failure was 419.1 ± 82.6 N in the PW group in comparison to 499.4 ± 109.6 N in the ISF group, P = .06. CONCLUSION: For TP tendon transfer, ISF and PW techniques were comparable, with no differences in tendon displacement after cyclical loading or load to failure. Greater variability was observed in the PW group, suggesting it may be a less reliable technique. CLINICAL RELEVANCE: The results indicate that early active dorsiflexion and protected weightbearing may be safe for clinical evaluation, with potential benefits for the patient compared with cast immobilization.